Disparity of Silaturrahmi Culture and New Way of Society on Globalization Era - Umi Hanik; A Zahid A Zahid (Lembaga penelitian dan Pengembangan Masyarakat (LPPM) IAIN Kediri, 2020)
Silaturrahmi is an Indonesian culture which is done as a form of gratitude for God's favor providing health for people. The form of old-silaturrahmi is by visiting relatives in turn anytime, but usually for Muslims, it is done during the big holiday, such as Eid al-Fitr and Eid al-Adha. Unlike rural communities, silaturrahmi culture is a moment inherent in daily life, as in rural communities known forÂ sambatan, rewang, mbecek, and ruwatan, actually not only those moments, when meeting neighbors and family usually take time to reprimand and sit together. This warmth is what is currently experiencing disparity in the development of technology that provides video call and chatting applications, such asÂ WhatsApp. It is technological development that shifts rural communities in the culture of silaturrahmi, thus existing of new way to facilitate the silaturrahmi of rural communities, this shift not only creeps into the pattern of silaturrahmi, but the values of religiosity and a new understanding of the culture of silaturrahmi in rural communities that become our homework together, so that the value of religiosity in silaturrahmi culture is still maintained.